Sistem Suhu dan Kelembapan Tanah Pada Tanaman Cabai Rawit Di Greenhouse Berbasis Internet OF Things (IOT) - Komaling, Jessa V; Santa, Kristofel; Moningkey, Efraim R. S. (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
The soil moisture monitoring system for cayenne pepper plants is an important part in ensuring optimal plant growth. The limited land that is often found makes the use of greenhouses one solution to deal with this problem. In this research, the system uses a soil moisture sensor which can measure soil moisture and a DHT11 sensor as an air temperature measurement with IoT-based monitoring. The integration of the NodeMCU ESP8266 with the Telegram platform is going well, marked by the success of the system in sending test result notifications automatically every time there is a change in soil moisture status and also local display via the 16×2 LCD making it easier for users if they want to check directly in the field. The test results show that the monitoring system built has met the basic needs for monitoring soil moisture in cayenne pepper plants in a small-scale greenhouse and can be an effective solution in supporting IoT-based agricultural activities. Keywords (Agriculture, Cayenne Pepper Plants, Greenhouse, Internet of Things, Soil Moisture)